Report on the intellectual ability of children living in high-fluoride water areas - Liu, S; Lu, Y; Sun, Z; Wu, L; Lu, W; Wang, X; Yan, S (Fluoride, 2008)
Sixty children, aged 10 to 12, were randomly selected for IQ testing from an area with high fluoride (3.15 mg F/L) in the drinking water along with 58 control children of the same age from a nearby low fluoride (0.37 mg F/L) area. The two areas are located approximately 5 km apart in the Tianjin Xiqing District, and both have similar normal iodine levels, living standards, access to medical facilities, economic development, educational level, etc. A single Individual using the C2 version of the Chinese Raven Test did the IQ testing. The mean IQ scores were significantly different: 92.27 plus or minus 20.45 in the high F area and 103.05 plus or minus 13.86 in the low F area (P<0.01). Within the seven categories of the scores, there were significantly more borderline and low IQs in the high F area (13/60) than in the low F area (2/58) (p<0.01).